Complexity, Reality and Ontological Insecurity: On Mistakes and Navigational Skills - Uribe-Lopera, Lucas; González, Sebastián (Conatus - Journal of Philosophy, 2024)
This article explores the concept of reality and the transformation concerning the complex approach to the modes of existence based on the interrelation between diverse actants that make up our world. Considering recent ontological debates and critiques of modernity, the article argues for a shift away from ready-made suppositions about reality and the desire for simplified answers. We propose a radical idea of an actant interaction perspective grounded in Bruno Latour’s and Hartmut Rosa’s ideas of exploring an ontology embracing curiosity, imagination, and the importance of making mistakes as necessary attitudes in navigating the uncontrollable nature of reality. The article emphasizes the importance of embracing a sense of liberty when comprehending and interacting with the world. It encourages us to concentrate on the strengths and connections of living organisms.